2006
DOI: 10.1620/tjem.210.239
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Administration Enhances the Healing of Lung Parenchymal Injuries and Reduces Air Leakage in Rats

Abstract: Beneficial effects of glutamine on wound healing are well known. Parenchymal injuries in the lung cause air leakage that resolves with wound healing. We aimed to determine the effect of glutamine on the healing of lung injuries. Wistar albino female rats were randomized in three groups. One group (control, n = 7) received intraperitoneal injection of 0.9% sodium chloride (1.5 ml /day), while other group (GLN, n = 7) received glutamine (1.5 g/kg/day), beginning two days prior to the operation for total four day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The GLN groups received IP injections of 1 g/kg GLN (HyClone) (0.05 g/ml) in saline suspension. The dose of GLN was chosen based on previous studies that showed positive effects when 1 g/kg or higher of IP GLN were used 47, 48. Saline or LPS and saline or GLN injections were given concurrently.…”
Section: Methodsmentioning
confidence: 99%
“…The GLN groups received IP injections of 1 g/kg GLN (HyClone) (0.05 g/ml) in saline suspension. The dose of GLN was chosen based on previous studies that showed positive effects when 1 g/kg or higher of IP GLN were used 47, 48. Saline or LPS and saline or GLN injections were given concurrently.…”
Section: Methodsmentioning
confidence: 99%
“…Reports have demonstrated the benefit of glutamine supplementation alone on wound collagen synthesis and accumulation in primary or secondary (36) wounds. Specifically, a study of air leak pressures after deliberate pulmonary laceration in a group of Wistar albino rats indicated that rats receiving glutamine supplementation had higher air leak pressures than control animals, and that these animals also had higher levels of immature collagen, as demonstrated by histopathology (37). A second study similarly demonstrated greater burst strength in colon anastomoses in rats with glutamine supplementation than those with glycine supplementation, and also noted higher levels of mature collagen in the anastomotic colon tissue of the glutamine group (38).…”
Section: Clinical and Preclinical Data Examining Nutrient Supplementamentioning
confidence: 99%
“…The dose of glutamine was also chosen based upon previous studies in rodents showing positive effects using 1 g kg −1 or higher i.p. glutamine (Prem et al 1999; Sanli et al 2006). Furthermore, our dose is within the range of effective doses (0.30–1.5 g kg −1 day −1 ) used in human clinical studies (Oliveira et al 2010; Wernerman, 2011).…”
Section: Methodsmentioning
confidence: 99%